Multi-species comparative analysis of the equine ACE gene identifies a highly conserved potential transcription factor binding site in intron 16. - Natasha A Hamilton; Imke Tammen; Herman W Raadsma (PLoS ONE, 2013)
Angiotensin converting enzyme (ACE) is essential for control of blood pressure. The human ACE gene contains an intronic Alu indel (I/D) polymorphism that has been associated with variation in serum enzyme levels, although the functional mechanism has not been identified. The polymorphism has also been associated with cardiovascular disease, type II diabetes, renal disease and elite athleticism. We have characterized the ACE gene in horses of breeds selected for differing physical abilities. The equine gene has a similar structure to that of all known mammalian ACE genes. Nine common single nucleotide polymorphisms (SNPs) discovered in pooled DNA were found to be inherited in nine haplotypes. Three of these SNPs were located in intron 16, homologous to that containing the Alu polymorphism in the human. A highly conserved 18 bp sequence, also within that intron, was identified as being a potential binding site for the transcription factors Oct-1, HFH-1 and HNF-3β, and lies within a larger area of higher than normal homology. This putative regulatory element may contribute to regulation of the documented inter-individual variation in human circulating enzyme levels, for which a functional mechanism is yet to be defined. Two equine SNPs occurred within the conserved area in intron 16, although neither of them disrupted the putative binding site. We propose a possible regulatory mechanism of the ACE gene in mammalian species which was previously unknown. This advance will allow further analysis leading to a better understanding of the mechanisms underpinning the associations seen between the human Alu polymorphism and enzyme levels, cardiovascular disease states and elite athleticism.